1992
DOI: 10.1164/ajrccm/145.5.990
|View full text |Cite
|
Sign up to set email alerts
|

Improved Outcome Based on Fluid Management in Critically III Patients Requiring Pulmonary Artery Catheterization

Abstract: We performed a randomized, prospective trial to evaluate whether fluid management that emphasized diuresis and fluid restriction in patients with pulmonary edema could affect the development or resolution of extravascular lung water (EVLW), as well as time on mechanical ventilation and time in the intensive care unit (ICU), in critically ill patients requiring pulmonary artery catheterization (PAC). PAC was performed on 101 patients. A total of 52 patients were randomized to an EVLW management group using a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
126
0
10

Year Published

1993
1993
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 522 publications
(140 citation statements)
references
References 22 publications
4
126
0
10
Order By: Relevance
“…EVLW may detect pulmonary edema early, and may be an indicator of mortality in acute lung injury or severe sepsis [71][72][73]. EVLW has been used to guide fluid management in acute respiratory distress syndrome and subarachnoid hemorrhage [74][75][76][77]. An important drawback to both systems, however, is that data interpretation is unreliable in the setting of common tachyarrhythmias like atrial fibrillation.…”
Section: Pulse Contour Cardiac Output Technologymentioning
confidence: 99%
“…EVLW may detect pulmonary edema early, and may be an indicator of mortality in acute lung injury or severe sepsis [71][72][73]. EVLW has been used to guide fluid management in acute respiratory distress syndrome and subarachnoid hemorrhage [74][75][76][77]. An important drawback to both systems, however, is that data interpretation is unreliable in the setting of common tachyarrhythmias like atrial fibrillation.…”
Section: Pulse Contour Cardiac Output Technologymentioning
confidence: 99%
“…Es muß jedoch betont werden, daß dieses Vorgehen bisher in keiner klinischen Studie überprüft wurde. Mitchel et al (18) haben jedoch zeigen können, daß eine ARDS-Therapie, die anhand der direkten Messung des EVLW geführt wird, im Vergleich zu einer Therapie, die sich in erster Linie am PCWP orientiert, zu einer verkürzten Beatmungsdauer und zu einem kürzeren Aufenthalt auf der Intensivstation führt.…”
Section: Measurement Of the Intrathoracic Blood Volume And Extrapulmounclassified
“…Clinical studies have demonstrated a reduced mortality rate in patients with ARDS in whom fluid removal and reduction of the capillary hydrostatic pressure were attainable; however, the praeter or propter of this observation is not clear at present [52,104,112,113,120]. In this regard, a therapeutic regimen guided by direct measurement of extravascular lung water may be superior to a management primarily addressing central venous and capillary wedge pressures [28,79]. A general recommendation for the concept of volume removal in the early exudative phase of ARDS [39,51,71] is, however, questionable for two reasons.…”
Section: Fluid Balance and Oxygen Transportmentioning
confidence: 99%